Does Politics Matter in the Conduct of Fiscal Policy? Political Determinants of the Fiscal Sustainability: Evidence from Seven Individual Central and Eastern European Countries (CEEC) - Redžepagić, Srdjan; Llorca, Matthieu (Panoeconomicus, 2007)
This paper aims at assessing the fiscal sustainability and its political determinants in seven Central and Eastern European Countries (CEEC), namely Estonia, Latvia, Lithuania, Poland, Slovenia, Slovakia and the Czech Republic. First, using the recent sustainability approach of Bohn (1998) based on fiscal reaction function, econometric findings using Ordinary Least Squares (OLS) reveal a positive response of the primary surplus to changes in debt in several countries. In other words, fiscal policy is sustainable in Baltic countries, Slovenia and Slovakia, but not in Poland and in the Czech Republic. Second, by introducing political dummy variables, we test the electoral budget cycle and the partisan cycle theories. We find the presence of electoral and partisan cycle in Poland but not in the rest of our countries.Key words: Fiscal reaction function, Public debt sustainability, Political budget cycles, Time series.JEL: E62, H62, P16.